2020
DOI: 10.1038/s41467-020-15447-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and continuous regulating adhesion strength by mechanical micro-vibration

Abstract: Controlled tuning of interface adhesion is crucial to a broad range of applications, such as space technology, micro-fabrication, flexible electronics, robotics, and bio-integrated devices. Here, we show a robust and predictable method to continuously regulate interface adhesion by exciting the mechanical micro-vibration in the adhesive system perpendicular to the contact plane. An analytic model reveals the underlying mechanism of adhesion hysteresis and dynamic instability. For a typical PDMS-glass adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…[7][8][9][10][11] Notably, although the gecko lizards can stick with an adhesion strength of more than 100 kPa, they can move in speeds as high as 0.8 m s −1 through their extraordinary adhesion switching capability. [12] DOI: 10.1002/marc. 202200012 As the glass used in the semiconductor or display manufacturing process becomes wider and thinner these days, the demand for a versatile pick-and-place system to transfer the objects is greatly mounting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11] Notably, although the gecko lizards can stick with an adhesion strength of more than 100 kPa, they can move in speeds as high as 0.8 m s −1 through their extraordinary adhesion switching capability. [12] DOI: 10.1002/marc. 202200012 As the glass used in the semiconductor or display manufacturing process becomes wider and thinner these days, the demand for a versatile pick-and-place system to transfer the objects is greatly mounting.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Remarkable trials using artificial dry adhesive for adhesion switching have been suggested, recently, a research group reported an interesting study of dry adhesive which is capable of extremely rapid adhesion switching by using microvibration. [12] Despite a lot of efforts, some lethal challenges that need to be overcome still exist, such as limits of the adhesion against rough surface profile, fragile repeatability, durability, and vulnerability to damages. [11,22,25] Therefore, the study for a new adhesion dry adhesive having not only good adhesion switching but also high adaptability onto the various surfaces is required.…”
Section: Introductionmentioning
confidence: 99%
“…Since microstructures placed in vertical positions can adhere to the substrate and disturb the entire structure [ 6 ], many studies have been conducted to dominate the surface forces at micro- and nanoscale in recent years. Shui et al [ 7 ] proposed a method to continuously regulate adhesion forces by creating mechanical microvibrations for a typical polydimethylsiloxane (PDMS) glass substrate. Their result indicated that the adhesion force could be increased or weakened 77 times using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…However, equal load sharing among these pillars also prevents them from being easily released. By considering the peeling deformation in gecko toe detachment, various climbing robots [36][37][38][39][40][41][42], transport grippers [43][44][45][46][47][48][49][50][51], and other functional devices [52][53][54][55] have been designed based on external field triggered reversible adhesion, such as mechanical [36-44, 52, 53], pressure [46,47,51], magnetic [45], thermal [48,49], and light [50] stimuli. Nonetheless, despite the high adhesion strength of single adhesive microstructures, these existing controllable adhesive systems are limited to smallarea (< 5 cm 2 ) surfaces and a lightweight (< 500 g) adhesion capacity, owing to the dilemma of supporting structures simultaneously realizing stiff backing and flexible peeling, particularly in large areas, thereby blocking the broad applications of reversible strong adhesion.…”
Section: Introductionmentioning
confidence: 99%